Self-Assembly of Short Amphiphilic Peptides and Their Biomedical Applications - Le, Xiaosong; Gao, Tianwen; Wang, Li; Wei, Feng; Chen, Cuixia; Zhao, Yurong (Current Pharmaceutical Design, 2022)
A series of functional biomaterials with different sizes and morphologies can be constructed through self-assembly, among which amphiphilic peptide-based materials have received intense attention. One main possible reason is that the short amphiphilic peptides can facilitate the formation of versatile materials and promote their further applications in different fields. Another reason is that the simple structure of amphiphilic peptides can help establish the structure-function relationship. This review highlights the recent advances in the self-assembly of two typical peptide species, surfactant-like peptides (SLPs) and peptides amphiphiles (PAs). These peptides can self-assemble into diverse nanostructures. The formation of these different nanostructures resulted from the delicate balance of varied non-covalent interactions. This review embraced each non-covalent interaction and then listed the typical routes for regulating these non-covalent interactions, then realized the morphologies modulation of the self-assemblies. Finally, their applications in some biomedical fields, such as the stabilization of membrane proteins, templating for nanofabrication and biomineralization, acting as the antibacterial and antitumor agents, hemostasis, and synthesis of melanin have been summarized. Further advances in the self-assembly of SLPs and PAs may focus on the design of functional materials with targeted properties and exploring their improved properties.
Keywords: peptides amphiphiles